2011
DOI: 10.2147/ijwh.s23179
|View full text |Cite
|
Sign up to set email alerts
|

Non-fistulous urinary leakage among women attending a Nigerian family planning clinic

Abstract: Video abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
5
4
1
Order By: Relevance
“…The common types of urinary incontinence recorded in this study were urgency (33.3%), stress (22.9%), and mixed (20.8%). This is consistent with findings from previous studies that identified stress, urgency and mixed incontinence as the three main subtypes of incontinence in women [ 12 , 13 , 17 19 ]. Studies however differ on which type is the most prevalent.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The common types of urinary incontinence recorded in this study were urgency (33.3%), stress (22.9%), and mixed (20.8%). This is consistent with findings from previous studies that identified stress, urgency and mixed incontinence as the three main subtypes of incontinence in women [ 12 , 13 , 17 19 ]. Studies however differ on which type is the most prevalent.…”
Section: Discussionsupporting
confidence: 93%
“…Studies however differ on which type is the most prevalent. This study identifies urgency incontinence as the commonest type similar to findings of Badejoko et al [ 17 ], but differs from other studies in the sub-region that identified stress incontinence as the most common [ 18 , 19 ].…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…[13,27] Severity of the symptoms is one of the reasons identified in previous studies as why women seek out for medical attention, conversely in this study majority of the women who leaked urine did so about 8 times a week. [26,27] A higher proportion of the study participant reported symptoms of stress UI which is comparable to other studies, [6,19,27,28] however the study by Ojengbede et al reported a higher proportion (13.7%) of women with urge incontinence in the same environment. [19] Remarkably, mode of delivery and education were not causal factors of UI in this study, although it was observed that majority of those with UI had increased parity and vaginal delivery.…”
Section: Discussionsupporting
confidence: 64%